Analyzing tasks assessed in university Calculus exams: a didactic and historical perspective - Calderón-Torres, María G. (2024)
[Objective] This study seeks to characterize mathematical tasks assessed in exams, with a focus on didactic features related to the meaning of the mathematical content they address, and their cognitive aspects. Additionally, it aims to describe the evolution of these features over time. [Methodology] In this longitudinal descriptive study, a content analysis of 568 mathematical tasks from 51 exams was conducted over 17 consecutive academic periods between 2014 and 2022. The analysis was conducted within the context of a Differential and Integral Calculus course taught at a university in Costa Rica. Information was organized and interpreted using a system of seven variables related to didactic features specific to the analysis of school-level mathematical tasks. [Results] The assessed mathematical tasks stand out for their variety of content and a predominance of verbal-symbolic representation, exclusively mathematical scientific situations, and cognitive demand at the level of procedures without connections. The predominance of exclusively mathematical scientific situations remained constant over time. However, from a certain point onwards, there was a tendency for verbal-symbolic representation and procedures without connections to decrease in favor of multiple representations and procedures with connections. [Conclusions] The assessed mathematical tasks partially reflect features related to the meaning of mathematical content and cognitive aspects essential for learning calculus. The evolution over time indicates progress in several features, although there is still ample room for improvement in others.